2011
DOI: 10.1093/rheumatology/ker201
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in knee and hip osteoarthritis: the role of pain and physical function

Abstract: Important levels of fatigue are common in knee and hip OA patients. After evidence-based tailored conservative treatment targeted to improve pain and physical function, a small decrease in fatigue levels was found. Reduction in levels of different fatigue dimensions were related to the change in physical function and pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 30 publications
3
37
1
1
Order By: Relevance
“…It is widely known that female have higher morbidity of RA than male, but we found that the incidence and degree of functional disability had no difference in gender. In addition, we found fatigue had no significant relationship with functional disability in regression, which was inconsistent with finding by the previous studies that fatigue was positively related to physical function [42,43]. These findings indicate gender and marital status make no difference in functional disability in southwest Chinese patients.…”
Section: Discussioncontrasting
confidence: 99%
“…It is widely known that female have higher morbidity of RA than male, but we found that the incidence and degree of functional disability had no difference in gender. In addition, we found fatigue had no significant relationship with functional disability in regression, which was inconsistent with finding by the previous studies that fatigue was positively related to physical function [42,43]. These findings indicate gender and marital status make no difference in functional disability in southwest Chinese patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, unspecified knee pain was associated with a 4.5-fold increased risk for decline in gait speed over 4 years [ 45 ]. Furthermore, WOMAC pain score was associated with greater physical fatigue, and fatigue was associated with poor physical function [ 35 ]. This may explain why the 20-m walk was not related to constant or intermittent pain, as the test may not be long enough to induce fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the distribution of pain VAS scores in patients who described their pain intensity as none, mild, moderate, or severe, the following cut points on the pain VAS were recommended: no pain (0-4 mm), mild pain (5-44), moderate pain (45-74 mm), and severe pain (75-100 mm) [36]. In addition, the patient global assessment of the severity of knee OA, measured on a 0-100 mm VAS, was evaluated where 0 equals no symptoms and higher scores indicating a lower response to therapy (or more severe the disease) [37]. Similar to pain status, patients marked the relevant severity of disease experienced on this line and the value was noted by the investigator, in mm [35].…”
Section: Clinical Status Assessmentmentioning
confidence: 99%